(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate the effectiveness of oral active oxygen gel, a topical oxygen-releasing agent, as an adjunctive treatment to conventional mechanical therapy in the management of periodontitis, focusing on the reduction of clinical inflammatory signs and the improvement of periodontal health. An integrative literature review was conducted using the PICO strategy to define the search criteria. The target population included patients with periodontitis; the intervention was the use of gel with active oxygen, compared to conventional treatment with scaling and root planing (SRP); and the outcome was the reduction of periodontal inflammation. The research was carried out in the PubMed database, selecting studies published between 2020 and 2025, following specific inclusion and exclusion criteria. Five relevant studies were included after screening and critical data analysis. The analyzed studies demonstrated that self-oxygenating composite hydrogel possesses antimicrobial and anti-inflammatory properties, contributing to the reduction of probing depth, gingival bleeding, and plaque index. Additionally, improved tissue healing and regeneration of periodontal tissues were observed, particularly in cases of moderate to severe periodontitis. The application of antimicrobial gel as a complement to conventional mechanical therapy proved effective in improving the clinical parameters of periodontitis. Its antibacterial and regenerative effects, associated with the controlled release of oxygen, present a promising alternative for periodontal treatment, although additional studies are needed to standardize usage protocols and assess its long-term effects.